Identifying the Personal Key Factors of Low Organizational Commitment in Course-Based Student-Composed Business Team - Gabriela Davinci Pehulisa; Anggara Wisesa; Irka Wijaya (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Studies showed that human resource is the key driver of the industry, especially in small businesses like start-ups. As a type of company that embodied a rapid disruption strategy, each member has their own paramount value to the team. To maintain a high-performing effective team, each member is required to have high organizational commitment, especially when the members are university students as there are plenty of self-development choices ahead. Therefore this research was conducted to find out what key factors that may decrease the level of organizational commitment. This research used a qualitative phenomenological approach where three informants from a course-based start-up were interviewed, in which the results were further analyzed through coding procedures. The analysis showed that (1) Industry interest; (2) Purpose of joining the company; and (3) Internalization of the company’s value are responsible to drive down members' commitment, either directly affecting, or through mediating and/or moderating variables of personal and/or organizational conditions.